Kritikalitas Pembagian Fungsi Pengawasan dan Regulasi antara Bank Indonesia, OJK, dan LPS - Ali Asdon Tanjung; Dafa Ariza; Feryanto Nababan; Raymond Panuturi Siboro; Hasyim Hasyim (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This study focuses on the effectiveness of supervision and regulation conducted by Bank Indonesia (BI), the Financial Services Authority (OJK), and the Deposit Insurance Corporation (LPS) in maintaining financial system stability in Indonesia. (LPS) in maintaining financial system stability in Indonesia. Through a qualitative qualitative approach with a literature review method, this research explores the role of each institution and identifies potential overlaps in each institution and identifies potential overlapping regulations that could affect national financial stability. can affect national financial stability. The results show that BI, through consolidated supervision and macroprudential policies, plays a significant role in maintaining monetary and financial stability. OJK, with its overarching mandate over the financial services sector, has implemented various regulations to ensure the integrity and stability of the financial system. to ensure the integrity and stability of the financial system. LPS contributes by guaranteeing customer deposits and handling failed banks, as well as coordinating with BI and OJK to maintain banking stability. with BI and OJK to maintain banking stability. To improve effectiveness, it is recommended to strengthen inter-agency coordination, regulatory harmonization, supervisory capacity, macroprudential policy, education and transparency, and international collaboration to maintain financial system stability, support sustainable economic growth, and improve public welfare.